2014
DOI: 10.5152/tjar.2013.55
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Maternal and Neonatal Effects of Combined Spinal Epidural Anesthesia in the Sitting or Lateral Position During Elective Cesarean Section

Abstract: Objective:Our goal was to demonstrate which position would be hemodynamically and technically better by comparing the effects of combined spinal epidural (CSE) in the sitting or lateral decubitus position for elective cesarean deliveries on maternal and neonatal parameters and ephedrine requirement.Methods: Sixty parturients were randomly assigned into two groups to perform CSE in the sitting (Group I, n=30) or right lateral decubitus position (Group II, n=30) using hyperbaric 10 mg bupivacaine and 20 µg fenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…[1] Of late many anesthetists have preferred using sitting posture of giving spinal anesthesia. [2,3,4] In this study a comparison is done on all parameters of spinal anesthesia effects after giving block in sitting and lateral positions. This article aims at establishing the facts and a review of the basics related to giving a spinal anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Of late many anesthetists have preferred using sitting posture of giving spinal anesthesia. [2,3,4] In this study a comparison is done on all parameters of spinal anesthesia effects after giving block in sitting and lateral positions. This article aims at establishing the facts and a review of the basics related to giving a spinal anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…the full version of 21 were retrieved after screening and detailed selection. Finally, 803 participants from 12 studies [7][8][9][10][12][13][14][15][16][17][18][19] were included in this metaanalysis. The flow chart of study selection was shown in Fig 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…The details of the study characteristics were shown in Table 1. Spinal anesthesia was performed in 5 studies [9,12,13,17,19], combined spinal-epidural anesthesia was performed in 7 studies [8,10,[14][15][16][17][18]. A total of 803 participants were enrolled, 415 patients from lateral position group, 388 patients from sitting group.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sitting or lateral positions are the standard positions used in parturients for subarachnoid blocks. [ 1 2 ] The landmarks of the spine can be easily identified in sitting positions and hence preferred in obese parturients. [ 3 4 ] Sitting position will reduce the lordosis of the spine seen in pregnancy and make spinal puncture easier.…”
Section: Introductionmentioning
confidence: 99%